2011
DOI: 10.1002/ccd.23269
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary interventions and cardiovascular outcomes for patients with chronic total occlusions

Abstract: Successful percutaneous CTO recanalization is not associated with survival free of death and cardiovascular hospitalizations in a contemporary population of patients with symptomatic coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Several previous observational studies and meta‐analysis regarding clinical outcomes in patients with successful CTO PCI have demonstrated its beneficial effect, such as improved survival rates and LV function, compared with failed PCI 1, 4, 5, 6, 8, 15. In contrast, some observational studies suggest that successful CTO PCI is not associated with improvement of survival rates and cardiovascular events 16, 17. Thus, these heterogeneous data obscure the necessity of PCI for CTO lesion, and thus it is important to assess whether a patient can gain beneficial effects from a CTO intervention before performing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous observational studies and meta‐analysis regarding clinical outcomes in patients with successful CTO PCI have demonstrated its beneficial effect, such as improved survival rates and LV function, compared with failed PCI 1, 4, 5, 6, 8, 15. In contrast, some observational studies suggest that successful CTO PCI is not associated with improvement of survival rates and cardiovascular events 16, 17. Thus, these heterogeneous data obscure the necessity of PCI for CTO lesion, and thus it is important to assess whether a patient can gain beneficial effects from a CTO intervention before performing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to find 23 observational studies comparing the desired clinical parameters between successful CTO recanalization and a strategy of medical management as a result of attempted but failed PCI . Of those, only two studies included a small number of patients (total of 27) who received pure medical management as PCI was not attempted due to unsuitable angiographic features.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the patients with CTO were referred for angiography because of persistent anginal symptoms or the presence of ischemia on noninvasive testing. Some studies included patients with ongoing unstable angina/acute coronary syndromes , but it is not clear from the records whether the CTOs in these patients were treated as primary culprit vessels or required simultaneous treatment as nonculprit vessels.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified white race as a predictor of a marginally higher CTO PCI success rate compared with non-whites. Only one single-centre study from the USA reported a comparator race,25 which were ‘African-American’, ‘Native American’ or ‘other’, while the US national registry and a single-centre study from the UK did not report these comparators 10 17. These racial differences may be due to increased cardiovascular risk factors associated with racial minorities, particularly in the USA 26.…”
Section: Discussionmentioning
confidence: 99%